Hybrid quantum-classical neural networks for real-time fault detection in power systems - Hina Hashmi; Aman Kumar; Shanu Rakesh Kuttan; Jhankar Moolchandani; Priya Goel; Aseel Smerat; Yaikob Abriham Massebo; Arshad Hashmi (PLoS ONE, 2026)
As modern power systems continue to be integrated with renewable energy sources, the ability to detect faults in these systems quickly and accurately is becoming more sophisticated. A Hybrid Quantum Classical Neural Network (HQCNN) model is presented in this paper that addresses the real-time fault detection challenge in transmission systems. A classical feature extractor, in this case a 1D CNN, and a quantum circuit are combined by the model, which aids in the classification of faults. Evaluations were conducted on simulated IEEE 14 and 39-bus system and on approximately 800 real PMU fault events. An accuracy of 96.43% on simulated data and 94.74% on real PMU data was achieved by the model, outperforming traditional deep learning models and maintaining detection times under 3 milliseconds. Various kind of fault like SDL (single line to ground), DL (double line), TP (three phase), and high-impedance faults, were correctly classified by the system. In a study in which elements of the model were removed, the quantum layer was found to be very important for improved performance. Issues like hardware limits and quantum noise were also looked at. As for the future, larger PMD data sets will be worked on, model explainability will be improved with hybrid XAI methods, and smaller HQCNN models will be developed for use in substation edge devices.